2015
DOI: 10.4269/ajtmh.14-0560
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Pediatric Fever in Western Kenya: A Case–Control Study of Falciparum Malaria, Respiratory Viruses, and Streptococcal Pharyngitis

Abstract: Abstract. In Kenya, more than 10 million episodes of acute febrile illness are treated annually among children under 5 years. Most are clinically managed as malaria without parasitological confirmation. There is an unmet need to describe pathogen-specific etiologies of fever. We enrolled 370 febrile children and 184 healthy controls. We report demographic and clinical characteristics of patients with Plasmodium falciparum, group A streptococcal (GAS) pharyngitis, and respiratory viruses (influenza A and B, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
34
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 32 publications
10
34
2
Order By: Relevance
“…For 20% of NP swabs and 33.3% of serum samples, no microbial species met our thresholds for detection. These proportions are consistent with previous reports [32,34,35,39].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For 20% of NP swabs and 33.3% of serum samples, no microbial species met our thresholds for detection. These proportions are consistent with previous reports [32,34,35,39].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in the above study, 9% of the children had malaria and 4.2% had bacteremia. In febrile children in Kenya, reported pathogens were spotted fever group Rickettsiae (22.4%), influenza (22.4%), adenovirus (10.5%), parainfluenza virus 1-3 (10.1%), Q fever (8.9%), RSV (5.3%), malaria (5.2%), scrub typhus (3.6%), human metapneumovirus (3.2%), group A Streptococcus (2.3%) and typhus group Rickettsiae (1.0%) [35,36]. Another study reported bacteremia in 19.1% of children admitted to a referral hospital in Uganda [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the East African region demonstrate that respiratory viruses account for the majority of febrile illness [1819], malaria was an infrequent cause of fever in Kenya (≤5%) [1920], and viral hepatitis was rare [18]. Unfortunately, data on these concomitant infections were not available for our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One patient who had neither a clinical nor a biologic malaria diagnosis was also treated with an antimalarial agent [97]. In a Kenyan study, 80% of all children who presented with acute febrile illness, including 72% of children with a negative malaria smear result, were prescribed antimalarial agents [13]. In a study performed in India, 33.8% of >1600 febrile patients received antimalarial drugs, 75% of whom had 1 negative malaria test result [98].…”
Section: Management Challengesmentioning
confidence: 99%
“…However, since the introduction of rapid diagnostics for malaria and implementation of malaria-control strategies in several countries, the number of diagnosed malaria cases has declined substantially [4][5][6][7][8][9]. As a consequence, the overdiagnosis of malaria and overtreatment in febrile illness has been increasingly recognized [10][11][12][13] and necessitates an improved understanding of nonmalarial causes of acute febrile illness [14].…”
mentioning
confidence: 99%